MANAJEMEN KEPALA SEKOLAH DALAM MELAKSANAKAAN SUPERVISI AKADEMIK DI SMA NEGERI 5 LUBUKLINGGAU - Muklis Riyanto Muklis Riyanto (UNIVERSITAS BENGKULU, 2015)
This study aimed to describe the management of school principals in implementingacademic supervision. The research method is a qualitative descriptive. Data collection techniquesused were observation, interviews and documentation. Data analysis techniques used is datacollection, data reduction, data presentation and conclusion. The conclusions of this study are (1)Planning academic supervision has been implemented according to the procedure. (2)Implementation of academic supervision implementation includes methods, media, and processingwas done coaching classes either by the principal. (3) Assessment academic supervision, evaluation,techniques and procedures have been done a good coaching by the principal. (4) Follow-up ofacademic supervision includes planning, implementation, and assessment, coaching has done goodby the principal.Keywords: management, academic supervision.